PLEISTOCENE ICE LIMITS IN THE RUSSIAN NORTHERN LOWLANDS - Astakhov V. (My University, 2004)
This chapter presents an explanatory note to the digitized map of ice limits compiled for the Russian North, beyond the limits of the Fennoscandian glaciation. Although the principal ice limits in Central Russia were already established at the beginning of geological mapping by the Emperor's Geological Committee in the late 19th century, the size of Pleistocene glaciers in the north and east, excluding the Fennoscandian ice dome, was poorly known until after extensive surveys of these remote areas in Soviet times. The maximum Pleistocene ice limit, related to pre- Eemian glaciations, has only undergone minor changes during the past some decades. However, younger ice limits have been under incessant stratigraphic discussion. The number of known ice limits in each given region depend very much both on the logistical accessibility and geographical peculiarities of the area. Several ice limits mapped in European Russia are hardly traceable beyond the Urals, because photogeology, the main tool in the north, does not produce good results in swampy lowlands. Also, topographically expressive ice marginal zones of the Central Siberian ice sheets cannot be directly connected with limits of the Barents-Kara ice sheets in the fiat West Siberian Plain.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен